Sparse matrix varieties, Daubechies spaces, and good compression regions of Grassmann manifolds - Collery, Brian, author; Peterson, Chris, advisor; Shonkwiler, Clayton, advisor; Cavalieri, Renzo, committee member; Kirby, Michael, committee member; Pouchet, Louis-Nöel, committee member (Colorado State University. Libraries, 2024)
The Grassmann manifold Gr(k, n) is a geometric object whose points parameterize k dimensional subspaces of Rn. The flag manifold is a generalization in that its points parameterize flags of vector spaces in Rn. This thesis concerns applications of the geometry of the Grassmann and flag manifolds, with an emphasis on image compression. As a motivating example, the discrete versions of Daubechies wavelets generate distinguished n-dimensional subspaces of R2n that can be considered as distinguished points on Gr(n, 2n). We show that geodesic paths between "Daubechies points" parameterize families of "good" image compression matrices. Furthermore, we show that these paths lie on a distinguished Schubert cell in the Grassmannian. Inspired by the structure of Daubechies wavelets, we define and explore sparse matrix varieties as a generalization. Keeping in that theme, we are interested in understanding geometric considerations that constrain the "good" compression region of a Grassmann manifold.
Keywords: Grassmann manifold; Daubechies wavelets